1998
DOI: 10.1016/s0166-2236(98)01275-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide-mediated excitability: a key triggering mechanism for seizure generation in the developing brain

Abstract: Most human seizures occur early in life, consistent with established excitability-promoting features of the developing brain. Surprisingly, the majority of developmental seizures are not spontaneous but are provoked by injurious or stressful stimuli. What mechanisms mediate 'triggering' of seizures and limit such reactive seizures to early postnatal life? Recent evidence implicates the excitatory neuropeptide, corticotropin-releasing hormone (CRH). Stress activates expression of the CRH gene in several limbic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
251
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 198 publications
(259 citation statements)
references
References 83 publications
(99 reference statements)
4
251
0
4
Order By: Relevance
“…Using specific probes directed against heteronuclear (unedited) CRH RNA, our 6 and other 17 groups have shown a rapid activation of the CRH gene in the immature rat hypothalamus after appropriate challenges. The half-life of heteronuclear CRH RNA is short, permitting resolution of gene activation and inactivation in the range of minutes.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Using specific probes directed against heteronuclear (unedited) CRH RNA, our 6 and other 17 groups have shown a rapid activation of the CRH gene in the immature rat hypothalamus after appropriate challenges. The half-life of heteronuclear CRH RNA is short, permitting resolution of gene activation and inactivation in the range of minutes.…”
Section: Discussionmentioning
confidence: 97%
“…32 More recently, in vitro studies have shown that CRH modulates glutamatergic mechanisms to increase excitatory neurotransmission in the hippocampal circuit. 6,25 Thus, under physiological circumstances, release of CRH may modulate hippocampal neurotransmission, augmenting glutamate-mediated alterations of hippocampal function. This may influence both normal hippocampal processes such as longterm potentiation and, when excessive, may promote abnormal excitation 1,6,25 and excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises the possibility that the HPA axis may be dysfunctional in hippocampal sclerosis and MTLE. The stress mediator, corticotrophin-releasing hormone (CRH), is present in these structures; although its functions there are not yet well understood, considerable evidence exists for a pivotal role for CRH in epileptogenesis in infancy and childhood (Baram and Hatalski, 1998). In a range of animal models, laboratory stressors and exposure to exogenous glucocorticoids result in structural and functional alterations in brain regions critically involved in MTLE, especially the hippocampus and amygdala (Gould et al, 2000;McEwen and Magarinos, 2001;Vyas et al, 2003).…”
Section: Introductionmentioning
confidence: 99%